Historical papers on the Janissaries 1886-1324 (Journal of the College of Basic Education, 2023)
We conclude through the research, that the establishment of the Janissaries came due to the problem of partisanship of the Ottoman army, and also it is an idea that was deliberated between Prince Alaa and Judge Qara Khalil. The other reason for the emergence of this army is the increase in the land seized by the Ottoman Empire as a result of its many wars. Some historical events are caused by the Janissaries of the Ottoman state were also presented, and we explained the extent of the influence of these forces on the political situation of the state, and in the end this formation was eliminated, after the power of the ruling authority met and the Ottoman people's repulsion from the Janissaries